Long-Term Effects of Tillage, Crop Rotations and Nitrogen Management Systems on Water Use Efficiency and Groundwater Quality - Kanwar, Ramesh; Bakhsh, Allah (Journal of Agricultural Engineering, 2011)
Increasing global population in the world is putting enormous pressure on available water resources and preservation of water quality. Therefore, sound policies with good incentives are needed to implement water conservation and pollution control practices, especially in areas of the world where major water bodies are already showing signs of degradation. To develop sustainable agricultural production practices, long-term studies were initiated in 1988 at Iowa State University to determine the effects of different tillage, crop rotation, and nutrient (fertilizer and manure) management systems on water use, crop yields, and nitrate–nitrogen (NO3-N) leaching losses to groundwater with the goal of mitigating environmental concerns of production agriculture. A three phase field study was conducted from 1988 to 2006 to investigate the impact of tillage systems (chisel plough and no-till), crop rotations (continuous corn and corn-soybean rotation), and nine N-management systems on NO3-N concentrations and leaching losses to tile water. The N-application rates of 202 and 168 kg-N.ha?¹ were applied during first (1988-1992) and third phases (2001-2006), and lower N rates of 135 and 110 kg-N.ha?¹ were applied in the second phase (1993-1998). Rotated corn resulted in better water use efficiency, significantly (p=0.05) higher corn grain yields, and lower NO3-N leaching losses compared with continuous-corn for all tillage systems. On the average, higher NO3-N concentrations were observed during first phase (20.7 mg.l?¹), followed by third phase (18.7 mg.l?¹) and second phase (10.5 mg.l?¹) due to higher N-application rates. Chisel ploughing increased corn grain yields and exited almost equivalent NO3-N leaching losses to tile water compared with no-till system. Effects of wet year after dry years and low plant N-uptake elevated NO3-N concentrations to as high as 32.8 mg.l?¹ in 1990 and 24.5 mg.l-1 in 2004. Fall applied manure and chisel ploughing had significantly higher NO3-N concentrations of 27 mg.l?¹ compared with 17.7 mg.l?¹ from no-till and spring applied manure. Results of this study showed that lower N application rates from UAN or manure in combination with chisel ploughing and corn-soybean rotation could be a good viable sustainable practice of farming.